Factors Affecting Breast Milk Output in Post Sectio Caesarea Mothers at RSUD Sultan Sulaiman Kab. Serdang Bedagai Year 2023 - Sukmawati Pasaribu; Deli Theo; Ramadhani Syafitri Nasution (Universitas Ibn Khaldun Bogor, 2024)
Breastfeeding brings joy to new mothers and provides the best start for children. However, this process is always easy, especially for mothers after cesarean delivery (SC). This research explores the factors that influence the release of breast milk (ASI) in post-SC mothers at Sultan Sulaiman Hospital, North Sumatra. In planning a cross-sectional survey, variables such as breastfeeding frequency, breast care, nursing care, diet, and gestational age were evaluated to understand overall breast milk production. The results show that regular breastfeeding frequency and good breast care are associated with smooth breast milk production. However, hospitalisation did not show a significant correlation with breast milk production in mothers after CS.